Hydrodynamics of Rotary Apparatus of The Wet Method of Dust Cleaning - Karimov Ikromali Tojimatovich; Madaliyev Akhror Nizomiddinovich; Isomidinov Azizjon Salomidinovich (European Science Publishing, 2023)
The article presents the device and principle of operation of the improved design of the contact element of the rotary apparatus for wet dust and gas cleaning. As a result of theoretical studies, formulas were derived for calculating local and hydraulic resistances and the total lost pressure created in the direction of movement of the dusty gas supplied to the apparatus. As a result, depending on the total pressure loss in the device, it is possible to determine the efficiency of gas and dust cleaning and determine the optimal hydrodynamic parameters of the device.
Keywords: dust gas, rotor, support grid, fibrous material, nozzle, diffuser, confuser, drop catcher.